ACADEMIC STAFF JOB EMBEDDEDNESS: MODEL DIMENSIONALITY AND VALIDATION IN TANZANIA’S UNIVERSITIES - Hokororo, Silver J.; Kitindi, Ernest; Michael, Francis (International Journal of Research -GRANTHAALAYAH, 2018)
Universities in Tanzania as many others in Africa and the globe are faced with the challenge of retaining their academic staff. This study examined the dimensionality and generalization of Job Embeddedness Theory, a promising perspective for understanding employee retention, in the context of academic staff in Tanzania’s universities. A survey of 314 members of academic staff from 2 Public Universities and 3 Private Universities was conducted, and Exploratory Factor Analysis (EFA) and Split Sample Cross Validation were used in determining the appropriate dimensionality and generalizability of Job Embeddedness Model in the context of study, respectively. Results indicated that that job embeddedness in the context of academic staff in Tanzania’s universities is a seven factors model. The results also indicate that seven variables out of 30 in the model were not stable, hence compromising generalizability of the model in the context of the study. It was recommended that, since Job Embeddedness Theory is a developing perspective, the volatile variables should be considered for revision or deletion in the future studies, before a seven-factor Job Embeddedness model is accepted for generalizability to larger population of academic members of staff in Tanzania’s Universities.